Prevalence of otomycosis in patients with cerumen impaction due to ear-phone usage during COVID-19 - Sunethra Suresh; Suraj Suresh; Sudha Sivasamy (Future Science, 2021)
Background: Otomycosis affects about 9% of patients with otitis externa. One of the predisposing factor is impacted cerumen. Earphone usage causes cerumen impaction. In the light of the recent COVID-19 pandemic, people are housebound due to prolonged lockdown. Hence people are more technology dependent as working from home and studying online has become the norm. Therefore, usage of earphones has proportionately increased, and the impacted cerumen cases have increased. Methods: This cross-sectional study aimed to analyze data from questionnaire to assess the prevalence of otomycosis among patients with impacted cerumen due to excessive earphone usage, establish associations between otomycosis and symptoms such as pain and hearing loss as well as the correlation between fungal growth and the long hours of earphones usage. The relationship between the age of participants and the usage of earphones during the pandemic was also explored. The data was collected from 100 individuals aged 14 to 51 years who sought treatment for symptomatic impacted wax at an ENT clinic in Malaysia. Results: The mean age of participants was 25.9 years. There was a 31% prevalence of otomycosis among these patients. Otalgia was present in 60% of patients with otomycosis (t value 2.94, coefficient 0.27). Approximately 37% of patients had a large air-bone gap indicating conductive hearing loss. There was an insignificant correlation between otomycosis and the longer hours of earphones usage (t value 1.51, coefficient 0.00015). No correlation was found between age of participants and the total hours of earphone usage (t value 0.63, coefficient 0.0012). Conclusion: This study offers initial evidence that earphone usage could be a predisposing factor in developing otomycosis. However, there was no evidence of longer hours of earphones usage increasing the chances of developing otomycosis. Additionally, symptoms like otalgia and conductive hearing loss could be present in both earwax impaction and otomycosis.